2011
DOI: 10.1371/journal.pone.0016235
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Porcine microRNAs in Multiple Tissues by a Solexa Deep Sequencing Approach

Abstract: The domestic pig (Sus scrofa) is an important economic animal for meat production and as a suitable model organism for comparative genomics and biomedical studies. In an effort to gain further identification of miRNAs in the pig, we have applied the Illumina Solexa sequencing technology to carry out an in-depth analysis of the miRNA transcriptome in a pool of equal amounts of RNA from 16 different porcine tissues. From this data set, we identified 437 conserved and 86 candidate novel miRNA/miRNA* in the pig, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
64
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 51 publications
(67 reference statements)
15
64
1
Order By: Relevance
“…One study deciphered a high number of novel porcine miRNAs along the intestine and suggested a crucial role of miRNAs in intestinal functions (37). Another study examined the porcine miRNA transcriptome in different tissues and found that miR-423-5p was widely expressed (38). We confirmed the NGS results showing the upregulation of miR-423-5p in lymphocytes of ileal lymph nodes in piglets of the probiotic group at 1 week postweaning that were fed a diet with E. faecium.…”
Section: Discussionsupporting
confidence: 71%
“…One study deciphered a high number of novel porcine miRNAs along the intestine and suggested a crucial role of miRNAs in intestinal functions (37). Another study examined the porcine miRNA transcriptome in different tissues and found that miR-423-5p was widely expressed (38). We confirmed the NGS results showing the upregulation of miR-423-5p in lymphocytes of ileal lymph nodes in piglets of the probiotic group at 1 week postweaning that were fed a diet with E. faecium.…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, Goren et al (20) did find enrichment of miR-423-5p in the exosomal fraction of patients with HF, indicating that the mechanism of miR-423-5p release may be different in patients with HF compared with healthy controls. In the pig, miR-423-5p was shown to be ubiquitously expressed, with high levels in heart, liver, and brain (55). Together with the detected upregulation of miR-423-5p in human failing myocardium (41,42), this suggests that circulating miR-423-5p in HF is derived from the myocardium.…”
Section: Heart Failurementioning
confidence: 82%
“…Small RNA fractions were isolated from a 15% denaturing polyacrylamide gel to obtain 19- to 24-nt molecules, and 15 μg was ligated to 5′- and 3′-proprietary adaptors without de-phosphorylation and re-phosphorylation. The samples were reverse-transcribed into cDNA, which was amplified using RT-PCR following the Illumina protocol, and the DNA was sequenced on a Solexa machine (Illumina) [13,24]. Solexa sequencing was performed at the Beijing Genomics Institute (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%